2019
DOI: 10.3390/app9132598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Addition on Mortars: Characterization and Photoactivity

Abstract: In this study, mortar specimens were prepared with a cement:sand:water ratio of 1:3:0.5, in accordance with standard EN196-1. Portland CEM I 52.5 R grey (G) and white (W) cements were used, together with normalised sand and distilled water. Different amounts of TiO 2 photocatalyst were incorporated in the preparation of the mortar samples. The effect of the addition of TiO 2 was studied on mechanical properties of the mortar and cement including compressive and flexural strength, consistency (the flow table te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Specimens of cement with an addition of 5 wt % of TiO 2 /N showed a final setting time that was about 57 min faster in comparison to the unmodified cement. A similar observation was made by Hernández-Rodríguez et al [37]; they added commercial TiO 2 P25 to CEM I 52.5 R and the results showed that the photocatalysts act as a setting accelerator.…”
Section: Resultssupporting
confidence: 83%
“…Specimens of cement with an addition of 5 wt % of TiO 2 /N showed a final setting time that was about 57 min faster in comparison to the unmodified cement. A similar observation was made by Hernández-Rodríguez et al [37]; they added commercial TiO 2 P25 to CEM I 52.5 R and the results showed that the photocatalysts act as a setting accelerator.…”
Section: Resultssupporting
confidence: 83%
“…The experimental results obtained in this study provide no evidence for any statistically significant variation in the mechanical properties or durability of pavement, which could be associated with the application of photocatalytic coatings or incorporation of photocatalytic materials into cementitious materials. This finding is in line with that of a previous study (Hernández-Rodríguez et al, 2019). The only pavement characteristic that is affected is the friction coefficient, which depends on many parameters such as the capacity to retain water, porous structure of the initial matrix, degree of hydrophilicity, and properties of the resulting photocatalytic surface.…”
Section: Main Indicator I2: Intrinsic Performancesupporting
confidence: 92%
“…On the other hand, the effect of TiO 2 addition to cementitious mass leads not only to photocatalytic activity, but also improves the mechanical properties of cementitious materials. The enhancement of mechanical properties by filling the pores and interaction with the other components of cement were observed [6,22,25].…”
Section: Introductionmentioning
confidence: 98%
“…Hernández-Rodríguez et al [22] proposed a partial replacement of the cement with TiO 2 . The photocatalyst was only incorporated into a one-centimeter-thick surface layer on the cementitious specimens.…”
Section: Introductionmentioning
confidence: 99%